Discourses on Violence in Costa Rica, El Salvador, and Nicaragua: Youth, Crime, and the Responses of the State - Peter Peetz (German Institute of Global and Area Studies (GIGA), 2008)
The paper analyzes the social construction of youth violence in Nicaragua, Costa Rica, and El Salvador on the one hand, and the related security policies of the three states, on the other. In each country, there is an idiosyncratic way of constructing youth violence and juvenile delinquency. Also, each country has its own manner of reaction to those problems. In El Salvador youths are socially constructed as a threat to security, and the state implements predominantly repressive policies to protect citizens against that threat. In Nicaragua and Costa Rica, where the social discourse on youth violence is less prominent, the state's policies are neither very accentuated nor very coherent, whether in terms of repressive or nonrepressive measures. There are strong relations and mutual influences between the public's fear (or disregard) of youth violence and the state's policies to reduce it. – – In diesem Beitrag wird einerseits die soziale Konstruktion von Jugendgewalt in Nicaragua, Costa Rica und El Salvador analysiert und andererseits die auf diese Problematik gerichtete Sicherheitspolitik der drei Staaten. Die Konstruktion von Jugendgewalt und Jugendkriminalität weist von Land zu Land unterschiedliche Charakteristika auf, und die drei Staaten reagieren jeweils anders auf diese Phänomene. In El Salvador werden Jugendliche als Sicherheitsbedrohung konstruiert, vor der die Gesellschaft mit vorwiegend repressiven Sicherheitspolitiken geschützt werden muss. In Nicaragua und Costa Rica, wo der gesellschaftliche Diskurs über Jugendgewalt weit weniger im Mittelpunkt der öffentlichen Debatte steht, sind die diesbezüglichen staatlichen Politiken weder sehr ausgeprägt noch sehr kohärent, gleich ob es sich um repressive oder nichtrepressive Maßnahmen handelt. Gesellschaftliche Angst vor (oder Nichtbeachtung von) Jugendgewalt und staatliche Sicherheitspolitik, um dieser Gewaltform zu begegnen, stehen miteinander in engem Verhältnis und üben gegenseitigen Einfluss aufeinander aus.
Keywords: 300; Central America; youth violence; security policies; discourse analysis